Factors Impacting the Provision of Antiretroviral Therapy to People Living with HIV: The View from Haiti. Issue 3 (April 2014) - Rouzier, Vanessa; Farmer, Paul E; Pape, Jean W; Jerome, Jean-Gregory; Van Onacker, Joelle Deas; Morose, Willy; Joseph, Patrice; Leandre, Fernet; Severe, Patrice; Barry, Donna; Deschamps, Marie-Marcelle; Koenig, Serena P
Haiti is the poorest country in the Western Hemisphere and has the highest number of people living with HIV in the Caribbean, the region most impacted by HIV outside of Africa. Despite continuous political, socioeconomic and natural catastrophes, Haiti has mounted a very successful response to the HIV epidemic. Prevention and treatment strategies implemented by the government in collaboration with non-governmental organizations have been instrumental in decreasing the national HIV prevalence from a high of 6.2% in 1993 to 2.2% in 2012. We describe the history and epidemiology of HIV in Haiti and the expansion of antiretroviral therapy (ART) over the past decade, with the achievement of universal access to ART for patients meeting the 2010 World Health Organization guidelines. We also describe effective models of care, successes and challenges of international funding, and current challenges in the provision of ART. We are optimistic that the goal of providing ART for all in need remains in reach.